(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In view of some practical situations in mind that idea of priority to one discipline over another discipline plays very important role to enhance the profit of the system, the motive of the present manuscript is to analyze a cold standby system by giving priority to preventive maintenance over repair. Two identical units are taken having two modes- operative and complete failure. There is a single server who visits the system immediately for conducting maintenance and repair. Server conducts preventive maintenance of the unit after a maximum operation time ‘t’. However, repair of the unit is done at its complete failure. Priority is given to preventive maintenance of one unit over repair of the other unit. The random variables associated with failure time, completion of maximum operation time, preventive maintenance and repair times are statistically independent. The failure time of the unit and the time by which unit undergoes for preventive maintenance and repair times are taken as arbitrary. Graphs are drawn to depict the behavior of MTSF, availability and profit function for particular values of various parameters and costs.